Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Alright! Let's solve the equation [tex]\( x^2 = 18 + 3x \)[/tex] step-by-step to find its roots.
1. Rewrite the equation in standard form: Move all terms to one side of the equation to set it equal to zero.
[tex]\[ x^2 - 3x - 18 = 0 \][/tex]
2. Apply the quadratic formula: Recall that for a quadratic equation of the form [tex]\(Ax^2 + Bx + C = 0\)[/tex], the solutions for [tex]\(x\)[/tex] are given by:
[tex]\[ x = \frac{{-B \pm \sqrt{{B^2 - 4AC}}}}{2A} \][/tex]
For our equation [tex]\( x^2 - 3x - 18 = 0 \)[/tex]:
- [tex]\(A = 1\)[/tex]
- [tex]\(B = -3\)[/tex]
- [tex]\(C = -18\)[/tex]
3. Calculate the discriminant: The discriminant [tex]\( \Delta \)[/tex] is:
[tex]\[ \Delta = B^2 - 4AC \][/tex]
Substituting the values:
[tex]\[ \Delta = (-3)^2 - 4(1)(-18) = 9 + 72 = 81 \][/tex]
4. Find the roots: Using the quadratic formula:
[tex]\[ x = \frac{{-(-3) \pm \sqrt{81}}}{2(1)} = \frac{{3 \pm 9}}{2} \][/tex]
This gives us two solutions:
[tex]\[ x = \frac{3 + 9}{2} = \frac{12}{2} = 6 \][/tex]
[tex]\[ x = \frac{3 - 9}{2} = \frac{-6}{2} = -3 \][/tex]
So, the roots of the equation [tex]\( x^2 = 18 + 3x \)[/tex] are [tex]\( x = -3 \)[/tex] and [tex]\( x = 6 \)[/tex].
Thus, the correct answer is:
[tex]\[ \boxed{x = -3, x = 6} \][/tex]
1. Rewrite the equation in standard form: Move all terms to one side of the equation to set it equal to zero.
[tex]\[ x^2 - 3x - 18 = 0 \][/tex]
2. Apply the quadratic formula: Recall that for a quadratic equation of the form [tex]\(Ax^2 + Bx + C = 0\)[/tex], the solutions for [tex]\(x\)[/tex] are given by:
[tex]\[ x = \frac{{-B \pm \sqrt{{B^2 - 4AC}}}}{2A} \][/tex]
For our equation [tex]\( x^2 - 3x - 18 = 0 \)[/tex]:
- [tex]\(A = 1\)[/tex]
- [tex]\(B = -3\)[/tex]
- [tex]\(C = -18\)[/tex]
3. Calculate the discriminant: The discriminant [tex]\( \Delta \)[/tex] is:
[tex]\[ \Delta = B^2 - 4AC \][/tex]
Substituting the values:
[tex]\[ \Delta = (-3)^2 - 4(1)(-18) = 9 + 72 = 81 \][/tex]
4. Find the roots: Using the quadratic formula:
[tex]\[ x = \frac{{-(-3) \pm \sqrt{81}}}{2(1)} = \frac{{3 \pm 9}}{2} \][/tex]
This gives us two solutions:
[tex]\[ x = \frac{3 + 9}{2} = \frac{12}{2} = 6 \][/tex]
[tex]\[ x = \frac{3 - 9}{2} = \frac{-6}{2} = -3 \][/tex]
So, the roots of the equation [tex]\( x^2 = 18 + 3x \)[/tex] are [tex]\( x = -3 \)[/tex] and [tex]\( x = 6 \)[/tex].
Thus, the correct answer is:
[tex]\[ \boxed{x = -3, x = 6} \][/tex]
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.